Practices and social representations of digital technology in the learning of French as a foreign language in South African universities - (:unkn) unknown (My University, 2023)
This study is rooted in work in language didactics and addresses the issue of digital practices among students learning French as a foreign language (FLE). Our aim is to grasp the issues at stake in terms of digital practices and social representations in situations of potential informal appropriation identified among a group of students at a university in South Africa, one of the African countries that have greatly developed their digital infrastructure. The aim of this PhD work is to answer the following questions: what are students' practices with digital tools outside the FLE classroom? What are the social representations linked to digital technology? What is the link between representations and practices? What similarities and differences are there between personal practices and FLE practices? To collect and analyze students' digital practices, we opted for a mixed-method approach combining a questionnaire-based quantitative survey and qualitative research based on semi-structured interviews. We sampled 169 students who were interviewed by means of a questionnaire with a view to collecting their practices and representations of the digital during their process of appropriating FLE, and eight students who were interviewed individually to gain a better understanding of their digital practices and the meaning they give to them. These results show that students are highly equipped. The main results also make it possible to identify the different types of personal practices that are most intense among students: relational and recreational practices. The results also describe the FLE practices most frequently used by students (French research, French text correction using online dictionaries and automatic correctors, vocabulary, grammar, translation and writing activities; reception and production), as well as the digital tools most frequently used (university platform, instant messaging, social networks, email). We also found that digital tools used fo
Keywords: African Research